Rethinking the Parenting Practices in Nepal: The Parental Discipline and Its Association with the Adolescents’ Psychological Wellbeing - Sharma, Sharada; Shakya, Nona; Ghimire, Sadikshya (Academia Journal of Humanities & Social Sciences, 2026)
Adolescence is a critical period of rapid physical, emotional, and social development. The parental discipline influences the adolescents’ psychological development, but their parents’ harsh behaviors to them can lead to the negative psychosocial outcomes. Therefore, the aim of this study is to identify the parental discipline and psychological wellbeing of the adolescents who are studying in different schools in Nepal. A descriptive cross-sectional study with the probability multi-stage random sampling technique was applied to select the sample. Data were collected using a structured, self-administered, and standard tool, using Ryff’s psychological wellbeing 18 items seven-point scale with six dimensions of well-being. They include autonomy, environmental mastery, personal growth, positive relations with others, purpose of life, and self- acceptance. The study employed descriptive (frequency, percent, mean, and standard deviation) and inferential statistics (Pearsons’s correlation and independent t test) for data analysis. Among the findings from the 201 adolescents, a total of 47.8% reported a positive perception of the parental discipline. The mean scores for the parental discipline and the psychological wellbeing were 101.38 ± 7.28 and 55.9 ± 9.18, respectively. The analysis indicated a statistically significant association between the parental discipline with the type of school and a strong negative correlation between the parental discipline and the adolescents’ psychological wellbeing (r=-.359, p=0.000). Additionally, no significant difference in the psychological wellbeing was found, in which the measurement was based on age, sex, birth order, type of family, and school. Less than half of the adolescents demonstrated a positive perception of parental discipline. Overall, the study showed a low psychosocial wellbeing; however, the strict discipline may negatively affect their adolescents’ psychological wellbeing. These findings highlight the importance of adopting the balanced and supportive parenting approaches.